(untitled) (Texas Journal of Engineering and Technology, 2022)
The article analyzes the essence, brief history, meaning, technology, designs of used machines, directions and prospects for the development of flexographic printing, and identifies the advantages and disadvantages of machines for flexographic printing. In addition, ways to eliminate shortcomings are described and directions for research work to improve this technology and machine are established.